PENGARUH NEPOTISME DAN MONEY POLITIK TERHADAP ELEKTABILITAS CALON LEGISLATIF PADA PEMILIHAN LEGISLATIF TAHUN 2024 (STUDI : CALON LEGISLATIF DPRD PROVINSI BENGKULU DAPIL KOTA DARI PARTAI AMANAT NASIONAL) - Eza Rio Renaldo; Bobby Mandala Putra; Evsa Wulan Suri (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2026)
Nepotism and money politics remain prevalent in legislative elections in Indonesia. This study examines the influence of nepotism and money politics on the electability of legislative candidates (Caleg) from the National Mandate Party (PAN) in the 2024 Bengkulu Provincial Legislative Election, Bengkulu City Constituency. Using a quantitative approach with a survey of 70 respondents registered as permanent voters (DPT), data were analyzed through simple and multiple linear regression. The results show that nepotism has a positive and significant effect on electability (t = 3.374, sig. = 0.001, R² = 0.143), and money politics also has a positive and significant effect (t = 3.688, sig. = 0.000, R² = 0.167). Simultaneously, both variables significantly influence electability (F = 1626, sig. = 0.000, R² = 0.980). Nepotism was evidenced by the involvement of the Acting Mayor of Bengkulu in campaigning for his wife, Dwi Ratnawati, who obtained 13,769 votes. These findings confirm that non-formal factors such as nepotism and money politics significantly shape voter behavior and candidate electability in the Indonesian legislative election context, while also posing serious risks to democratic quality.